How early career pharmacists understand resilience – a qualitative study of experiences, challenges and strategies - Halimi, Syafiqah Nadiah; Rowett, Debra; Whitfield, Karen M.; Luetsch, Karen (ScienceDirect, 2022)
Introduction Resilience assists healthcare professionals in negotiating challenges, remaining positive when experiencing adversity, and in constructively dealing with difficult work situations and environments. There is increasing research about how early career healthcare professionals, understand and maintain resilience but little is known about support early career pharmacists may need and value.